Degradation of Free-Space Quantum Communication Under Dust Aerosol Conditions - Dipayon Bachar; Tanjoy Mahmud; Hasibul Hasan shanto; Sayeda Raisa Ilma (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
Quantum communication offers unprecedented security based on quantum mechanics principles. However, atmospheric factors significantly challenge free-space channels. This study investigates optical quantum signal degradation under dust aerosol conditions. Analyzing absorption and scattering characteristics, we evaluate link attenuation, channel bit error rate, particle concentration, and transmission distance. We examine channel capacity and fidelity across three quantum noise models: depolarization, amplitude damping, and bit-flip channels. Simulations show that particle concentration and transmission distance uniquely impact each channel. Consequently, free-space quantum communication performance is degraded to varying degrees by dust aerosols, emphasizing the need for robust environmental mitigation strategies